1996
DOI: 10.1021/ja952408f
|View full text |Cite
|
Sign up to set email alerts
|

Trihalomethyl Cations and Their Superelectrophilic Activation1

Abstract: Ab initio molecular orbital and density functional theory (DFT) calculations were performed to investigate energies, geometries, and reactivities of halomethyl cations and their protonated analogues. On the basis of calculated energies the observed superelectrophilic activation of the halomethyl cations in superacid solutions is discussed. The protonated halomethyl cations have considerable kinetic and thermodynamic stability. 13C NMR chemical shifts of selected systems were calculated by IGLO method and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 18 publications
(20 reference statements)
6
52
0
Order By: Relevance
“…[49] A similar case is seen in the isodesmic reaction of trichloromethyl cation (138) and the protosolvated superelectrophile (139) with propane (MP4-A C H T U N G T R E N N U N G (STDQ)/6-31G*//MP2/6-31G* + ZPE level; Figure 28). [50] In accord with experimental observations, hydride transfer to the superelectrophile 139 provides the 2-propyl cation (a charge-separated product) more favorably than does the monocationic electrophile (138). In a similar respect, charge separation can occur in reactions with arene nucleophiles.…”
supporting
confidence: 66%
“…[49] A similar case is seen in the isodesmic reaction of trichloromethyl cation (138) and the protosolvated superelectrophile (139) with propane (MP4-A C H T U N G T R E N N U N G (STDQ)/6-31G*//MP2/6-31G* + ZPE level; Figure 28). [50] In accord with experimental observations, hydride transfer to the superelectrophile 139 provides the 2-propyl cation (a charge-separated product) more favorably than does the monocationic electrophile (138). In a similar respect, charge separation can occur in reactions with arene nucleophiles.…”
supporting
confidence: 66%
“…These authors have shown that CCl 3 + is an excellent reagent for the generation of cations from alkanes and cycloalkanes in the SbF 5 matrix [28]. Nonempirical calculations of the trihalomethyl-and related di-and trications, CX 3 + , CX 2 +2 , CX +3 , which in principal could be generated from polyhalomethanes in the presence of proton superacids, have been described [29].…”
Section: Polyhalomethanes In the Presence Of Protic And Lewis Acids mentioning
confidence: 99%
“…65 The generation of these cations was also used by various teams 66,67 to initiate selective low temperature alkane activation. When these cations are generated in superacidic media, a protosolvation induces a superelectrophilic character, which was supported by Olah on the basis of high-level ab initio calculations.…”
Section: ð2:15þmentioning
confidence: 99%